How many miles to Babylon? : travels and adventures to Egypt and beyond, 1300 to 1640 - Wolff, Anne (Liverpool Science Fiction Texts., 2003)
How Many Miles to Babylon? uses the writing of European travellers to Egypt between c. 1300 and c. 1600 to give a picture of the country in the late medieval and early Renaissance periods, drawing on sources that have hitherto been inaccessible to English-speaking audiences. These accounts portray an Egypt ruled by the despotic Mamluk sultans and the early Ottoman governors, a society at once cruel and sophisticated, dangerous and alluring. The Europeans? wonderment at the exotic flora and fauna, the ancient ruins of temples and pyramids, and the astonishing summer rise of the Nile to irrigate.